Lider kullanıcı metodunun ürün geliştirme performansına etkisi ve bir uygulama - (:unkn) unknown (My University, 2010)
Etkili ve güçlü ürün geliştirme, müşteri ihtiyaçlarının doğru olarak analiz edilmesine bağlıdır. Müşteriyi ürün geliştirme proseslerine dâhil eden firmalar, pazarda büyük bir rekabet avantajı elde edeceklerdir. Yeni ürün geliştirme proseslerine müşterinin daha sık dâhil edilmesi, yeni ürünlerin pazara çıkma hızı üzerinde olumlu etkiye sahiptir. Bu bağlamda, pazarların en önemli müşterileri olarak görülen lider kullanıcılar da yeni ürün kavramları ve dizaynları elde etme çalışmalarında, müşteri ihtiyaçlarını analiz etmede önemli ihtiyaç ve çözüm bilgisi sağlarlar. Müşteri ihtiyaçlarının artmasından ve hızlı değişiklik göstermesinden dolayı kilit müşterilerin ürün geliştirme proseslerine dahil edilmesi özellikle otomotiv sektöründe oldukça önemlidir. Bu çalışmada, yeni ürün fikirlerinin üretilmesi prosesine müşterinin dâhil edilmesi, lider kullanıcı kavramı ve metodu ele alınmıştır. Lider kullanıcı metodunun temel uygulama adımları ve bu metodun kullanılmasındaki kritik başarı faktörlerine yer verilmiş ve ürün geliştirme performansı açıklanmıştır. Bu çalışma kapsamında, lider kullanıcıların ürün geliştirme prosesine dahil edilmesinin ürün geliştirme performansı üzerindeki etkilerini incelemek amacıyla otomotiv yan sanayinde faaliyet gösteren 51 firmayı kapsayan bir anket çalışması yapılmıştır. Elde edilen veriler SPSS 11.0 istatistik programı kullanılarak değerlendirilmiştir. Değerlendirme kapsamında; faktör analizi, güvenilirlik analizi, korelasyon ve regresyon analizi yapılmıştır. İstatistiksel analiz bulguları incelendiğinde, ürün geliştirme performansı ile lider kullanıcıların ürün geliştirme prosesinde yer alması değişkeni arasında anlamlı ve pozitif yönde bir ilişkinin olduğu tespit edilmiştir.

As a result of increasing competitive pressures together with continuously increasing costumers needs, decreasing production costs and product development times urge companies to adept a systematic product development process. As the product are designed and produced for the costumers, costumer views are vital for the design and it dictates a close collaboration with the costumers. In order to meet their increasing customers’ needs, today many companies are seeking the ways to reflect their costumers’ voices and requirements into their products and services. A product development process based on rapid, non-problematical and costumer voices will provide companies a market success through developed products and services. An effective new product development process depends on the definition of uneasy customer problems. In today’s competitive environment, companies are utilising different methods to define costumers’ needs and to develop products accordingly. Nowadays companies are incorporating the lead users having the abilities to see the general future trends of the market and getting important solutions to these future market needs. In this way, the companies both define the changing costumer needs and getting important competitive advantages by entering their products to the market in shorter times. In this study, firstly the importance of the inclusion of the costumers to the creation of new product development process is outlined, the lead user concept is defined, and the lead user method is explained and the importance of this method in product development studies is underlined. Secondly, the main application steps of the lead user method, namely definition of definition of lead users and lead user characteristics, creation of product concept with lead users and lead users’ product concept test are outlined in detail. Finally, the success factors in the application of this method are examined and the product development performance scales are explained. In the application stage of the work, a theoretical model explaining the effect of inclusion of the lead users into product development process was developed. As a result of continuously improvement of automotive technology and increase in customers’ expectations, the automotive sub-industry has to develop new product and improve the performance of the product they develop. Automotive sub-industry is one of the high value added industries in sustainable, social and economical development of a society and from this perspective it is highly important for Turkey. In this respect, a market survey with a questionnaire in automotive sub-industry was conducted in order to define the effects of lead users considered in the product development process performance independent variable on product development performance dependent variable in the theoretical model. According to the State Statistical Institute (DİE) and Small and Medium Industry Development Organisation (KOSGEB) criterion, 51 out of 210 small and medium sized companies active in automotive sub industry in and around Istanbul and Gebze were responded positively to our questionnaire. 27 of these responded companies were contacted with face-to-face method and 27 of the remaining companies were responded via e-mail. The characteristics of these companies participated in the study are detailed in presented tables. The information gathered from the field survey was analyses with SPSS 11.0 statistical analysis software. In the statistical analysis, it is determined that the dependent and independent variables in the factor analysis are ascertained in the related factors, the scales developed in the reliability analysis are rather reliable. The analysis also revealed that in the correlation analysis there is a meaningful and positive relationship between dependent and independent variables and with the help of simple linear regression analysis it was determined the variable of the inclusion of the lead users in the product development process affects the product development process in high meaningful level and positive manner. Under the light of the current study, the effects of the inclusion of the lead users in the product development process are interpreted from automotive sub-industries perspective. The comments made on this sectoral basis could be considered as a guideline for other companies and the researches.
Effects of lead user method on product development performance and a case study